2018
DOI: 10.26817/16925777.425
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment Literacy for Pre-service Teachers: Course Expectations from Different Stakeholders

Abstract: In the field of applied linguistics, for the past fifteen years, there have been discussions about language assessment literacy (LAL) —the knowledge, skills, and principles related to assessing language ability— (Davies, 2008; Fulcher, 2012). However, the field lacks research on the professional development of language teachers, particularly pre-service language teachers, through training in language assessment. Our paper focuses on the preliminary findings of an action research study whose goal is to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…As Fulcher states, the fact that the respondents were self-selected may account for this result. This sentiment is also observed in the studies by Vogt and Tsagari (2014) and Yan, Fan, and Zhang (2017) with in-service teachers in Europe and China respectively; and Giraldo and Murcia (2018) with preservice teachers in Colombia. The results then beg the question of whether these teachers do indeed think all of the items they see in questionnaires are truly important for their lal.…”
Section: Challenges In Researching Teachers' Lal: From Constructs To supporting
confidence: 65%
See 3 more Smart Citations
“…As Fulcher states, the fact that the respondents were self-selected may account for this result. This sentiment is also observed in the studies by Vogt and Tsagari (2014) and Yan, Fan, and Zhang (2017) with in-service teachers in Europe and China respectively; and Giraldo and Murcia (2018) with preservice teachers in Colombia. The results then beg the question of whether these teachers do indeed think all of the items they see in questionnaires are truly important for their lal.…”
Section: Challenges In Researching Teachers' Lal: From Constructs To supporting
confidence: 65%
“…On the one hand, teachers are expected to possess quite a wide array of knowledge, skills, and principles, as several authors have emphasized (Fulcher, 2012;Giraldo, 2018b;Inbar-Lourie, 2013a;Stabler-Havener, 2018). On the other hand, research has consistently shown that pre-and in-service language teachers need and want training across the board (Fulcher, 2012;Giraldo & Murcia, 2018;Vogt & Tsagari, 2014). Additionally, current studies have started to shed light on the complexity of lal in its sociocultural milieu, that is, language teachers' institutional contexts of assessment (Hill, 2017;Scarino, 2013;Sultana, 2019).…”
Section: Why a Focus On Languagementioning
confidence: 99%
See 2 more Smart Citations
“…In ideal circumstances, when an assessment instrument is given to students, there should be no glitches: Sound systems should work properly, there are enough test copies for students, seating arrangements deter cheating, and there exist no background noises that can annoy students, among others. Even though teachers seem to discourage test administration as an important dimension of language assessment (see reports by Fulcher, 2012;Giraldo & Murcia, 2018;Vogt & Tsagari, 2014), administration is a key moment in the assessment enterprise.…”
Section: Theoretical Frameworkmentioning
confidence: 99%